Exploring the Role of Dermatoglyphics in Learning- A Case Study - Dhankar, Charu (International Journal of Social Sciences and Management, 2015)
The nature nurture issue has been an important debate in all aspects of the individual development. According to Jensen’s heritability ratio, hereditary has an impeccable influence in the development process. Based on these, dermatoglyphics has been used in the present case study in order to observe the innate potential of an individual, to give parents an insight into their child’s hidden potential and to groom them effectively. The present case study is confined to the acquiring methods and unique quotients of the subject. The findings of the study revealed the unique quotients of the subject and the best suitable acquisition method for the subject. Aim/Purpose: To test the methods of learning and unique quotients of the subject with the help of Dermatoglyphics Multiple Intelligence Test DMIT. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 301-303 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12651